Case Report: One Left Sinonasal Mass Suspect Benign - Nurfadilla Nurfadilla (Faculty of Medicine University of Malikussaleh, 2022)
Abstract Neurofibromas are benign peripheral nerve sheath tumors. They arise from schwann cells and fibroblasts of the connective tissue of the endothelium. Of the 25% to 45% neurofibromas that arise in the head and neck region, only 4% involve the nasal cavity and paranasal sinuses. Here we report one such case in a 18 years old male who presented to us with complaints of swelling n his left cheek since a year ago which often felt to shrink and then enlarge again and also complains of several other symptoms like watering of the left eye frequently, nasal obstruction, and also crooked tooth. The mass was histologically confirmed to be a neurofibroma, but Computer tomography and panoramic image leads it to dentigerous cyst.